Therapeutic modulation of retinoid X receptors – SAR and therapeutic potential of RXR ligands and recent patents. (3rd August 2019) - Schierle, Simone; Merk, Daniel
ABSTRACT: Introduction : Retinoid X receptor (RXR) agonists have a limited role in cancer therapy with bexarotene and alitretinoin as approved drugs but their use is limited by adverse effects. Several evidence from in vitro, in vivo, and small clinical studies points to various further potential applications of RXR ligands in neurodegenerative and inflammatory diseases. Areas covered : The authors review known RXR ligand classes with their key structure–activity relationships and recent reports on pharmacological effects of RXR modulation. Based on these aspects, the authors evaluate recent patents claiming novel RXR ligands or their use. Expert opinion : While the use of RXR modulators has been claimed in several novel and promising indications, little progress has been made in the development of innovative rexinoids with improved (subtype-)selectivity. Next-generation RXR modulators that selectively target the RXR subtypes for individual indications may be required to exhaustively exploit the therapeutic potential of RXRs.